Characterization and analysis of an oil‐in‐water emulsion stabilized by rapeseed protein isolate under pH and ionic stress. (20th June 2020) - Wu, Jin; Xu, Feiran; Wu, Ying; Xiong, Wenfei; Pan, Mengmeng; Zhang, Na; Zhou, Qi; Wang, Shijie; Ju, Xingrong; Wang, Lifeng
Abstract: BACKGROUND: Presently, identifying natural compounds as emulsifiers is a popular topic in the food industry. Rapeseed protein isolate (RPI) is a natural plant protein with excellent emulsifying properties, but it has not been systematically developed and utilized. RESULTS: This study investigated the surface hydrophobicity, wettability, and protein solubility of RPI to further explain its emulsifying behavior in emulsion systems. Nanoemulsions stabilized by RPI at varying protein concentration, pH, and ionic strength were prepared. The size distribution, zeta potential, flocculation index, creaming index, microstructure, rheology, and protein secondary structure of emulsions were measured. The emulsion stabilized by 20 g L −1 RPI at pH 10.0, 200 mmol L −1 ionic strength revealed an appropriate droplet size of 555 nm and the most internal gel strength without creaming phenomenon. Circular dichroism spectroscopy showed a positive correlation between emulsion stability and α ‐helix ratio, indicating the environment factors affected emulsion stability by acting on its hydrogen bonds. CONCLUSIONS: This study demonstrates that RPI is a practical emulsifier for stabilizing nanoemulsions. About 20 g L −1 RPI can stabilize 100 mL L −1 oil in water; stable emulsions can be formed at most pH conditions (except 7.0); ion addition will aggravate the emulsion flocculation, but also increase the internal gel strength. © 2020 Society of Chemical Industry